Bioremediation of acetamiprid and sulfoxaflor co-contamination by Ensifer sp. DA6 and characterization of a novel nitrile hydratase involved - Yang, Wenlong; Kang, Jia; Shao, Yahui; Geng, Yun; Zhang, Yingxin; Liu, Renlu; Chen, Gao (Frontiers in Microbiology, 2025)
IntroductionThe co-contamination of acetamiprid (ACE) and sulfoxaflor (SUL) threatens ecosystem security, yet their microbial remediation remains unexplored.MethodsThe bacterium Ensifer sp. DA6, which transforms ACE to IM-1-2 and SUL to X11719474, was isolated. Its genome was analyzed, and the nitrile hydratase (NHase) gene cluster was heterologously expressed in E. coli. The NHase was purified and modeled.ResultsImmobilized Ensifer sp. DA6 degraded ACE and SUL in Yellow River water. The recombinant E. coli and purified NHase both acquired ACE/SUL degradation ability. The NHase is a cobalt-containing enzyme with a and β subunits plus an accessory protein, and its active site was predicted.DiscussionThis is the first report on microbial co-degradation of ACE and SUL, identifying a novel NHase as the key enzyme, providing a potential bioremediation strategy.